2014
DOI: 10.3892/ijmm.2014.1996
|View full text |Cite
|
Sign up to set email alerts
|

Sulindac attenuates valproic acid-induced oxidative stress levels in primary cultured cortical neurons and ameliorates repetitive/stereotypic-like movement disorders in Wistar rats prenatally exposed to valproic acid

Abstract: Accumulating evidence suggests that anti-inflammatory agents and antioxidants have neuroprotective properties and may be beneficial in the treatment of neurodevelopental disorders, such as autism. In the present study, the possible neuroprotective properties of sulindac, a non-steroidal anti-inflammatory drug (NSAID), were investigated in vitro using cultured cortical neurons with valproic acid (VPA)-induced neurotoxicity, as well as in vivo through the behavioral analysis of rats prenatally exposed to VPA as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
(42 reference statements)
4
11
0
Order By: Relevance
“…In VPA exposure rats, the levels of WNT1 and WNT2 in the prefrontal cortex and hippocampus are up-regulated (Kalkman, 2012). Down-regulation of the Wnt signaling pathway attenuates the susceptibility to autism-like phenotypes in VPA-exposed mice (Zhang et al, 2012) (Zhang et al, 2015). Consistent with these reports, our study showed that Wnt signaling was over-activated in VPA-exposed rats, and inhibition of Wnt signaling by sulindac relieved ASD-like behaviors.…”
Section: Discussionsupporting
confidence: 93%
“…In VPA exposure rats, the levels of WNT1 and WNT2 in the prefrontal cortex and hippocampus are up-regulated (Kalkman, 2012). Down-regulation of the Wnt signaling pathway attenuates the susceptibility to autism-like phenotypes in VPA-exposed mice (Zhang et al, 2012) (Zhang et al, 2015). Consistent with these reports, our study showed that Wnt signaling was over-activated in VPA-exposed rats, and inhibition of Wnt signaling by sulindac relieved ASD-like behaviors.…”
Section: Discussionsupporting
confidence: 93%
“…However, treatment with NAC did not appear to affect the nuclear and cytoplasmic β-catenin levels, or the phosphorylation of β-catenin and GSK-3β, thus suggesting that the Wnt pathway may not be involved in NAC-mediated amelioration of autism-like behavior in VPA-treated rats. These results are in accordance with our previous in vitro study, which demonstrated that NAC reduced oxidative stress in primary neuronal cultures following pre-treatment with VPA without affecting the activity of the Wnt pathway (45). These findings suggested that the unaltered activity of the canonical Wnt pathway may be an indirect consequence, of reduced oxidative stress in VPA-exposed offspring followed by NAC administration.…”
Section: Discussionsupporting
confidence: 93%
“…Wnt and its associated signaling proteins have been identified as targets for GSH (44), whereas NAC has been demonstrated to inhibit the activation of the canonical Wnt pathway in the retinas of diabetic rats (43). Furthermore, previous studies have reported a critical role for the Wnt pathway in the pathogenesis of autism (23,28,45). In a previous study by the present authors, VPA was revealed to inhibit the phosphorylation, and thus the inactivation, of β-catenin, which is a key effector during canonical Wnt signaling, possibly through the upregulation of WNT1 and WNT2 expression, thereby activating the canonical Wnt pathway (46).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of exploratory behaviour, rearings decreased at 400-600 mg/kg (i.p. or s.c.; Table 1), except in one study where it increased [52]. No changed parameters were seen to cause this [52].…”
Section: Core Asd Behaviour 2: Repetitive Behaviours Open Field Testsmentioning
confidence: 87%
“…or s.c.; Table 1), except in one study where it increased [52]. No changed parameters were seen to cause this [52]. Locomotion gave mixed results across the doses, with some having increased locomotion (hyperlocomotion), others having decreased locomotion (hypolocomotion; Table 1).…”
Section: Core Asd Behaviour 2: Repetitive Behaviours Open Field Testsmentioning
confidence: 95%